The Relationship Between Education and Health: Reducing Disparities Through a Contextual Approach - Zajacova, Anna; Lawrence, Elizabeth M (Annual review of public health, 2018)
Adults with higher educational attainment live healthier and longer lives compared with their less educated peers. The disparities are large and widening. We posit that understanding the educational and macrolevel contexts in which this association occurs is key to reducing health disparities and improving population health. In this article, we briefly review and critically assess the current state of research on the relationship between education and health in the United States. We then outline three directions for further research: We extend the conceptualization of education beyond attainment and demonstrate the centrality of the schooling process to health; we highlight the dual role of education as a driver of opportunity but also as a reproducer of inequality; and we explain the central role of specific historical sociopolitical contexts in which the education-health association is embedded. Findings from this research agenda can inform policies and effective interventions to reduce health disparities and improve health for all Americans.